Profiles of Internet Buyers in 20 Countries: Evidence for Region-Specific Strategies - Lynch, Patrick D.; Beck, John C. (Journal of International Business Studies, 2001)
The prospect of an emerging global Internet consumer entices many internationalizing organizations as it would enable standardization of Internet strategies on a worldwide basis. A sample of advanced Internet users from 20 countries shows differences in beliefs, attitudes, perceptions, and Internet buying behavior depending on user experience, and home country or region. There were important differences after controlling for social, cultural and macro-economic variables. Implications for a regional approach to global e-commerce strategies are discussed.